THE EFFECTIVENESS OF CONTEXT CLUES TO TEACH VOCABULARY - Kurniawati, Suma; Sudarsono, Sudarsono; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to investigate the effectiveness of Context Clues to teach vocabulary. This research was conducted to Year – 8 students of SMP N 4 Sungai Raya in Academic Year 2018/2019. This research was pre-experimental design with pre-test, post-test and three times of treatments. The data were collected using a multiple choice test. The sample of the research was taken from Year – 8 Class C which consists of 30 students. The finding of the research showed that the mean score of the students’ pre-test was 5I.96 while the post-test was 70.8. It showed that the achievement of the students increased after the treatment was conducted. In this research, the researcher used the t-table a (0.05) with degree of freedom 29 is 1.699 meanwhile, the result of the t-test is 10.35 it means the t -test was higher than the t-table (10.35 > 1.699). The result of the effect size (ES) was 1.81 which was categorized as a strong effect. It showed that null hypothesis was rejected and the alternative hypothesis was accepted. It was also prove that using Context Clues affects significantly the students’ vocabulary mastery. Keywords: Context Clues, Pre- Experimental Research, Vocabulary